Effect of Mutations on Employee Job Satisfaction At Bulog Subdivre Parepare - Ummi Ditami yunas; Andi Aslinda; Muh. Rizal S (Public Resource Innovation Management and Excellence, 2025)
This study aims to determine how the effect of mutations on employee job satisfaction at Bulog parepare subdiv. This study uses a type of quantitative research. The data collection technique used is through observation data collection, interviews and questionnaires. The sample used in this study is the entire population, namely 53 employees. The data obtained from the results of the research were processed using data analysis and using the help of the SPSS version 25 software program which consisted of validity tests, reliability tests of research instruments as well as descriptive statistical analysis techniques and inferential statistical analysis of the data that had been obtained.The results showed that the indicators used for each variable indicated that the mutation variable had a significant effect on employee satisfaction at Bulog Subdivre Parepare. This is proven based on simple linear regression and the Coefficient of Determination Test on the data that has been obtained.